Trabalho escravo nas fazendas do Estado do Pará - FERNANDES, Luciana Sá (2012)
This paper examines a kind of economic rationality of the forms of slave labor in contemporary Brazil. This engaging system is sustained by the availability of workers, by threat, physical coercion, and terror. The present research aims at establishing links between the capitalist expansion in the southeastern State of Pará and the increased number of reports on slave labor and the governmental policies during the military regime. The paper examines the conjugation of these elements and the possibility of understanding the dynamics of slave labor a common practice in that region.